The Influence of Service Quality and Determination Price of Implications of Satisfaction on Customer Loyalty of PT. Tama Anugerah Mandiri - Marcelino, Reza; Ahadianto, Muhammad Sayakfika; Malau, April Gunawan; Fahcruddin, Imam (Dinasti Publisher, 2025)
This study aims to analyze the influence of service quality and pricing on customer satisfaction and its implications on customer loyalty at PT. Tama Anugerah Mandiri, a company operating in the ship agency sector. The main problem identified is the low level of customer satisfaction due to variations in service quality and perceptions regarding ship agency service pricing. This research employs a quantitative approach with an explanatory research design. The population consists of 90 customers, and the entire population was used as the sample through a saturated sampling technique. Data were collected using questionnaires measuring customers' perceptions of service quality, pricing, satisfaction, and loyalty. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships among variables simultaneously. The results indicate that service quality has a positive and significant effect on customer satisfaction, and competitive pricing also enhances satisfaction. Customer satisfaction acts as an intervening variable that strengthens the influence of service quality and pricing on customer loyalty. These findings emphasize the importance of appropriate service and pricing strategies to maintain customer satisfaction and loyalty in the ship agency industry